A percepção ambiental dos agricultores da Lagoa do Apodi-RN - Nascimento, Paloma Joyce do (Universidade Federal Rural do Semi-Árido, 2018)
Throughout the history of humanity, it has been observed that water consumption has increased progressively, through the multiplicity of uses of water resources, with emphasis on agricultural activities. In regions of limiting climatic conditions, such as the Brazilian Semi-arid, water scarcity gains notoriety due to socioeconomic and environmental conflicts. In the mentioned region, the Apodi-RN Lagoon is located, which presents environmental and socioeconomic importance for the municipality of Apodi, from its multiple uses throughout the year, with emphasis on agriculture, fishing, navigation, landscape harmony, maintenance of fauna and flora, leisure, construction, recreation, among others. In this sense, the present study has the general objective to carry out socioeconomic and environmental diagnosis of agricultural activities in the surroundings of the Apodi-RN Lagoon. In order to carry out this analysis, a semi-structured questionnaire was applied to 47 pond farmers. It was verified that agricultural practices result in environmental impacts related to deforestation, use of pesticides and fires. It was found that farmers are very concerned about the degradation of the water resource, where they indicated that human activities are the main contributor to pollution. In view of this scenario, environmental management of the study area is necessary through the diagnosis of the activities utilized in the investigated environment, strategic planning of the environmental sustainability actions of the analyzed area and management of the environmental programs for this reservoir.
Keywords: Recursos hídricos; Impactos ambientais das atividades agropecuárias; Conflitos ambientais; Water resources; The environmental impact of agricultural activities; Conflicts; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA